Mothers’ Satisfaction with Planned Vaginal and Planned Cesarean Birth - Blomquist, Joan L. (2011)
We sought to describe maternal satisfaction with childbirth among women planning either cesarean or vaginal birth. We enrolled primiparous women planning cesarean birth and a comparison group planning vaginal birth. After delivery, the maternal subjective experience was assessed with a visual analogue satisfaction scale and the Salmon questionnaire, with scale scores for these aspects of the maternal experience of birth: fulfillment, distress, and difficulty. The sample included 160 women planning vaginal birth and 44 women planning cesarean. Eight weeks postpartum, women planning cesarean reported higher satisfaction ratings (p = 0.023), higher scores for fulfillment (p = 0.017), lower scores for distress (p = 0.010), and lower scores for difficulty (p <0.001). The least favorable scores were associated with unplanned cesarean (n = 48). Women planning cesarean reported a more favorable birth experience than women planning vaginal birth, due in part to low satisfaction associated with unplanned cesarean. Maternal satisfaction with childbirth may be improved by efforts to reduce unplanned cesarean, but also by support for maternal-choice cesarean.